Application of UPFC on stabilizing torsional oscillations and improving transient stability - Alharbi, Yasser; Abu Siada, Ahmed; Abdou, A (AUPEC, 2013)
This paper investigates the application of Unified Power Flow Controller (UPFC) to stabilize multi-mode torsional oscillations of sub-synchronous resonance (SSR), and to improve the transient stability during a three phase short circuit fault that may result in oscillatory torques on the generator rotor shaft causing serious damages to the system and may call for the disconnection of a wind farm to avoid any possible damages. Simulation is carried out using MATLAB/Simulink software. Results show that the proposed UPFC controller is very effective in damping all SSR modes of the system under study and in minimizing the potential for the wind farm disconnection during the studied faults. The proposed controller is simple and easy to be implemented.